Architectural dialogue between historic charm and urban modernity (Architecture Image Studies, 2024)
The paper investigates the intricate relationship between historic charm and urban modernity to examine how architectural design can balance the scale between the preservation of cultural heritage and accommodation for contemporary needs. It examines methods through which modern structures could be inculcated into historically significant settings without affecting their genuine or aesthetic appeal. The paper discusses different case studies that range from projects where traditional and modern architectural elements coexist, allowing for a truly historic yet innovative environment. Key themes to be addressed in the paper are the adaptive reuse of historic buildings, preservation's role in urban planning, and advanced technologies used to revitalise and enhance landmark spaces. The research further addresses the socio-cultural and practical challenges of balancing preservation with urban development by proposing actionable frameworks for architects, urban planners, and policymakers. This study culminates in a call to elicit a dynamic dialogue between the past and the present as evolving urban landscapes maintain cultural depth and visual coherence.